Brain Vacuolation Resulting From Administration of the Type II Ampakine CX717 Is An Artifact Related to Molecular Structure and Chemical Reaction With Tissue Fixative Agents. (15th December 2017) - Purcell, Richard; Lynch, Gary; Gall, Christine; Johnson, Steven; Sheng, Zhong; Stephen, Michael Rajesh; Cook, James; Garman, Robert H; Jortner, Bernard; Bolon, Brad; Radin, Daniel; Lippa, Arnold
Abstract: Ampakines are small molecule positive allosteric modulators of the alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA). One class II ("low impact") ampakine, CX717, has been implicated to have a neurotoxic effect based on findings in nonclinical, long-term toxicity studies. The neurotoxicity concerns, which halted the clinical development of the molecule, arose due to a finding of extensive white matter vacuolation in multiple brain regions of animals that were administered high doses of CX717 in several test species (unpublished data). This work characterized the features and a potential mechanism by which ampakines induce vacuoles in brain tissue. Brain sections from adult rats given CX717 (750 mg/kg BID by oral gavage) exhibited no vacuoles with acute or short-term dosing. However, after 14 or more days of treatment, vacuoles were prominent in cerebellum, globus pallidus, and hippocampus. Vacuole margins were lined by glial fibrillary acidic protein (GFAP), and by transmission electron microscopy were shown to be astrocyte processes. CX717-associated vacuoles occurred in formaldehyde-fixed specimens but not flash-frozen samples. Time-course experiments showed that brain tissue slices from CX717-treated animals exhibit no vacuoles until immersed in formaldehyde fixative, whereupon vacuoles form and expand in a time-dependent manner. Chemical interactions in test tube experiments have demonstrated that the combination of CX717 and formalin in an aqueous solution produces an exothermic reaction. Taken together, the data indicate that CX717 does not induce vacuoles in vivo, but rather is associated with astrocyte vacuolation post mortem, likely as the ampakine reacts with formalin to produce gas pockets in brain parenchyma.